Development of an experimental model of a solar-wind chimney for electrical supply - Velazco Lorenzo, Dinau (2022)
An experimental model of a wind solar chimney for electrical supply was developed, firstly, the most suitable geographic space was selected for the implementation of the model. Next, we carried out a study in order to determine the environmental, wind and solar parameters using the viewers of the Ministry of Energy and Mines; Taking renewable energy resources as a starting point, a pre-dimensioning was established in order to guarantee economic and technical viability to be able to build the model.The theory of similarity was applied to define the preliminary geometry of the chimney considering built plants as referents, marking the difference of adding two additional subsystems, one wind and the other photovoltaic in order to give it greater autonomy; the wind subsystem located in the upper part of the chimney and the photovoltaic subsystem along the outer surface of the chimney collector and in the central part. Thermal fluid modeling was carried out in the collector considering the differential control volume applying the Reynolds transport equations, mass, moment, energy using Bousnik approximations in order to be able to determine the evolution of pressure, density and temperature working with a simplified model. of heat input in the collector, taking into account the radiation per square meter instantaneous in the place. Then the simulation was carried out in Matlab and satisfactory results of the model were obtained, with respect to the wind and photovoltaic subsystems, the simulations were developed to guarantee the energy contribution. The chimney components began to be designed considering the ease of transport, assembly handling, drawing the plans considering structural strength parameters, the anchoring component and the first chimney body; the number of bodies was established to achieve the design height. The collector was articulated to the first body of the chimney through 12 sectors which were built with structural T and with the design slope, to later cover it with standard transparent plastic number 12 and glue it to the collector. At the same time, the wind subsystem was designed, consisting of two wind turbines with an aerodynamic fuselage, blades with a NACA 624 profile. The foundation of the anchor was made and later the installation of all the bodies in which speed, temperature and humidity sensors of the chimney were installed considering wind turbines. Then the centralized system of accumulation, regulation and monitoring in the form of a column outside the collector was installed and the tests were carried out. The objective of developing the self-sufficient integral model was met considering 3 supply subsystems, in the collector temperature gradients were obtained significant, but according to the research schedule, the test dates corresponded to the month of August, where there is not a high level of radiation, which was expected from the beginning of the project, this did not generate a sufficient gradient for the operation of the thermal turbine. The photovoltaic and wind subsystems worked as expected in the experimentation area.